(untitled) (Texas Journal of Medical Science, 2024)
In the context of increasing aridization of lands in Central Asia, caused by global climate change, it is necessary to actively select plants that are resistant to water deficiency. One such species is the Goji medicinal shrub (L. chinense Mill. and L. barbarum L.). Goji exhibits high adaptability to various climatic conditions, especially dry ones. Its ability to grow in low-moisture conditions makes it a valuable resource in regions with limited access to water. This research plays a key role in creating sustainable and efficient approaches to agriculture in the face of a changing climate and a deteriorating environment.